In vitro Evaluation of Dentifrice with Low Fluoride Content Supplemented with Trimetaphosphate - Takeshita, E. M.; Castro, L. P.; Sassaki, K. T.; Delbem, Alberto Carlos Botazzo [UNESP] (Karger, 2009)
One way to reduce dental fluorosis is by reducing the fluoride (F) concentration in dentifrice, but low-F dentifrice should be as effective as a standard dentifrice. This study evaluated in vitro whether the supplementation with sodium trimetaphosphate (TMP) of a dentifrice with low F content (500 mu g/g) would provide a similar effect to that of a standard dentifrice. Bovine enamel blocks were submitted to a pH cycling regime incorporating daily exposures to a slurry of dentifrice: a low-F dentifrice with or without 0.1-3.0% TMP; an F-free, phosphate-free dentifrice (negative control), or a dentifrice with 1,100 mu g/g F (positive control). The addition of TMP to dentifrice with or without F was associated with higher surface hardness and decreased loss of integrated subsurface hardness after pH cycling. The combination of 1% TMP and 500 mu g F/g had a greater effect than the positive control dentifrice. It is concluded that the addition of TMP to the 500-mu g F/g dentifrice allowed a similar or larger effect as compared with a standard dentifrice in this in vitro model. Copyright (C) 2009 S. Karger AG, Basel
Keywords: Demineralization; Dental enamel; Dentifrice; Fluoride; pH cycling; Trimetaphosphate